The Three-Dimensional Perception of Reality in Evangelical Christianity - Liutkevičius, Eugenijus (Vilnius University Open Series, 2025)
In this chapter, I set out to explore the transcendental perceptions among Baptists in Ukraine. I am concerned with how Baptist believers perceive the world. Particularly I am interested in how they perceived the world as consisting of a transcendent quality aside from the dimensions of space and time. To discuss the interaction of these three modes of perceiving I coined the term ‘three-dimensional perception of reality’. This concept is defined as the believers’ ability to incorporate narratives and symbols from the Bible into their everyday life, and interpret both personal stories and global events accordingly. This will be exemplified through my ethnographic cases.